Brown marmorated stink bug current or planned research to prevent its establishment and to reduce its impact in New Zealand - Teulon, D.A.J.; Leskey, T.C.; Duthie, C. (New Zealand Plant Protection, 2016)
Brown marmorated stink bug (BMSB; Halyomorpha halys) originates from Asia and is currently spreading rapidly throughout the world but is not yet recorded in the southern hemisphere BMSB has a wide host range and in some regions it has become a major nuisance and a plant pest of significant economic importance for some fruit vegetable and ornamental crops Since 2014 raised awareness of BMSBs potential destructive impact in New Zealand and increasing border interceptions have led to a greater focus on research required to prevent its establishment and to reduce its potential impact Key contributions in developing BMSB research priorities and activities for New Zealand have come from several sources including an MPI Risk Assessment (2012) a keynote presentation at the 2014 B3 Conference several Ministry for Primary Industry/Department of Conservation/industry/researcher workshops methodical engagement of international BMSB experts and a crossMPI preparedness project Research has been initiated or is planned across the biosecurity spectrum to answer key questions about risk assessment pathway risk management diagnostics surveillance and eradication